Symptoms of Pepper Fruits Infested with Dipterous Pests and Their Control by Soil Treatment - AHMED, MOSTAFA KAMAL (The Libyan Journal of Agriculture, 2023)
Pepper fruits are attacked by the lonchaeid fly. Lonchaea aurea Macq. and the Mediterranean fruit fly. Ceratitis capitula (Wiedemann). Larvae from both species tunnel inside fruit tissues, and only specie, which develop in the fruit. Peppers were not attacked until they became about 3.5 cm long and 2.5 cm in diameter. Peppers attacked by Medfly larvae kept their shape and rigidity. But those infested with the lonchaeid larvae became soft and watery. Early symptoms of infestation showed small, creamy round scars about 1.0 mm in diameter. Infested parts became tender and soft areas gradually increased. The fruits then lost shape, all green tissues turning to a thin paste, that accumulated inside the skin at the bottom of the fruit. Some infested fruits dried on their plants. Pirimphos-methyl proved more effective as a soil treatment against the pupae of both insects than formothion. L. aurea was more sensitive than the Medfly. LC50 of pirimphos-methyl were 9.6 and 10.96 for both species respectively, and LC50 for formation were 26 and 59 respectively.